Embedding Religious Characters in Elementary School Through E-Learning Materials - Rokhmatul Yunita Aini (AL-ISHLAH: Jurnal Pendidikan, 2022)
Technological advances make it easy for teachers to build and design teaching materials with character values such as religious values. Creative teachers can use various multimedia technologies to present teaching materials that can transfer character values in every communication process, attitude and behaviour during online learning activities. This study aims to determine the extent to which religious characteristics are instilled in elementary schools through e-learning teaching materials. The design in this study is descriptive qualitative research. The research data was taken from observation and interviews. The participants involved were Religious teachers and students at the Pungging District Elementary School. The results showed that religious character values in electronic teaching materials presented by Religious teachers were seen in classroom activities such as praying, praying dhuha and memorizing juz amma. In addition, the interaction communication built by the teachers has made it easier for students to understand the religious values of each teaching material being taught. While the level of creativity of the teachers from the teaching materials used can be seen in the use of multimedia technology. The results of the study have implications for Religious teachers' understanding of the design of teaching materials by utilizing multimedia technology that can contain character values, with an attractive appearance and increase interest in learning